Crisis of Liability for Medical Injuries - Global Trends Aimed at Remedying Damage Caused during a Medical Treatment - Michal Bialkowski (Communications of International Proceedings, 2020)
The aim of the paper is to present changes occurring in the area of liability for medical injuries through the lens of experiences of Poland, New Zealand and Sweden. Basic research methods applied in the paper are the legal comparison method and the method of interpretation of applicable law. The paper presents transformations that have occurred in the Polish legal order around the traditionally understood tort liability for medical injuries and two proven out-of-court systems of pursuing claims for damages known from Sweden and New Zealand. Insurance, i.e. indemnity insurance and patient-injury insurance, takes a special place in legislative works that aim at facilitating the patient in obtaining the compensation pay. The increasing role of insurance, a transformation in understanding tort liability and its function allow an assumption that the future of tort liability departs from the principle of fault and repression directed against the injuring party. The main task that legislators face is to create conditions in which the patient obtains the payment regardless of the doctor’s fault. This is why the experience of New Zealand or Sweden should be an inspiration to create good and financially balanced no-fault systems.
Keywords: No-Fault System; Compensation; Insurance; Medical Error; Health Care System